Memórias de egressas da escola normal Duque de Caxias (Caxias do Sul/RS - 1949/1951) : formação de professores para a prática da higiene - Tonietto, Roberta Angela (My University, 2020)
In this study, we sought to investigate how the issue of hygiene was developed in the training of teachers of the Teacher Training Course that worked in Duque de Caxias Teacher Training chool- Caxias do Sul/RS. Increasing urbanization and strong industrialization, recurring in the established time frame, demanded changes in the behavior of the population, as the number of morbidity and mortality was increasing. The scholars of the time saw in the school possibilities to develop concepts that could contribute to disseminate ideas of hygiene, civility and healthy habits. The main objective of the research was to analyze representations of Hygiene from memories of former students of Duque de Caxias Teacher Training School, and aimed at answering the following leading question: Which representations of hygiene are evidenced in documents and memories of former students of Duque de Caxias Teacher Training School between the years of 1949 and 1951? Therefore, in this research, I seek to prioritize elements of Cultural History, valuing the representations of school culture, habits, senses and meanings attributed to hygiene practices in teacher training. The dissertation is organized in four chapters. The first one covers the initial considerations to introduce the reader to the issue, problem, objectives, time frame and research regarding hygiene. In the second one, I describe how the methodological path was developed, the data collection, done mainly in the Municipal Archive João Spadari Adami, the interview was carried out with two students from Duque de Caxias Teacher Training School, who started their courses in 1949, and finished in 1951. Then, in the third chapter, I develop the hygiene context scenario in the scope of health and education, as well as the teacher training movements for hygienist practices. In the fourth section, I describe movements of Teacher Training Schools and teachers’ training; I also introduce memories and documents related to Duque de Caxias Teacher Training School. The analysis of practices within the subject of Hygiene in Duque de Caxias Teacher Training School allowed me to reflect on the disciplining of the body and its gestures and hygiene in the school curriculum. From the memories of graduates and documents, it is possible to consider that the School's daily life and curriculum of Duque de Caxias Teacher Training School showed evidence of representations of imposition of discipline, unification, creation of habits and the social function developed by teachers in school activities with possibilities for creating school cultures. In addition, the discipline of Hygiene was prescribed in the Teacher Training Organic Law of1946, in the transcript of Edelweiss, and was practiced in teacher training at Duque de Caxias Teacher Training School between the years of 1949 and 1951. Possibly, the historical moment in which Brazil was passing through contributed to movements such as this one, of hygienist practices, advocating and being introduced in primary schools. Therefore, normal education should enable educators to develop the necessary knowledge, assigning meanings to hygiene.
Neste estudo, buscou-se investigar como a temática da higiene era desenvolvida na formação dos professores do Curso Normal que funcionava na Escola Normal Duque de Caxias - Caxias do Sul/RS. A urbanização crescente e a forte industrialização recorrentes no recorte temporal estabelecido exigiam mudanças de comportamento da população, pois o número de morbidades e mortalidade estava aumentando. Os estudiosos da época viram na escola possibilidades para desenvolver conceitos que pudessem contribuir para disseminar ideias de higiene, civilidade e hábitos saudáveis. O objetivo principal da pesquisa foi analisar as representações da Higiene a partir de memórias de egressas da Escola Normal Duque de Caxias e buscou responder à seguinte questão norteadora: Que representações da higiene se evidenciam nos documentos e nas memórias de egressas da Escola Normal Duque de Caxias entre 1949 e 1951? Busco, então, nesta pesquisa, priorizar elementos da História Cultural, valorizando as representações da cultura escolar, os hábitos, os sentidos e significados atribuídos às práticas da higiene na formação de professores. A dissertação está organizada em quatro capítulos. O primeiro abrange as considerações iniciais, situando o leitor em torno do tema, problema, objetivos, recorte temporal e uma pesquisa com relação à higiene. No segundo, descrevo como foi desenvolvido o percurso metodológico, a coleta dos dados, feita principalmente no Arquivo Municipal João Spadari Adami, as entrevistas realizadas com duas egressas da Escola Normal Duque de Caxias que iniciaram o curso de formação de professores em 1949, tendo concluído o mesmo em 1951. Em seguida, no terceiro capítulo, desenvolvo o cenário de contexto da higiene no âmbito da saúde e da educação, bem como os movimentos de formação de professores para as práticas higienistas. Já na quarta seção, descrevo as movimentações das Escolas Normais e a formação de professores, bem como apresento as memórias e documentos relacionados à Escola Normal Duque de Caxias. A análise das práticas da disciplina de Higiene na Escola Normal Duque de Caxias me permitiu realizar reflexões acerca da disciplinarização do corpo e seus gestos e a Higiene no currículo escolar. A partir das memórias de egressas e de documentos é possível considerar que o cotidiano e o currículo da Escola Normal Duque de Caxias tinham indícios de representações da disciplinarização, unificação, criação de hábitos e a função social desenvolvida pelos professores nas atividades escolares com possibilidades de criação de culturas escolares. Além disso, a disciplina de Higiene estava prescrita na Lei Orgânica do Ensino Normal de 1946, no histórico escolar de Edelweiss, e foi praticada na formação de professores da Escola Normal Duque de Caxias entre os anos de 1949 e 1951. Possivelmente, o momento histórico em que o Brasil vinha passando contribuiu para que movimentos como este, das práticas higienistas, preconizassem e fossem introduzidos nas escolas primárias. Logo, o ensino normal deveria habilitar os educadores para desenvolver o conhecimento necessário, atribuindo sentidos à higiene.
Keywords: Escolas; Professores - Formação; Higiene - Prática; Memória; Schools; Teachers, Training of; Hygiene - Practice